The progenitor of SN 2023ixf from hydrodynamical modeling - Bersten, Melina Cecilia (2024)
Context. The supernova (SN) 2023ixf is among the nearest Type II SNe discovered in recent decades. As such, there is a wealth of observational data of both the event itself and of the associated object identified in pre-explosion images. This has enabled variety of studies aimed at determining the SN properties and the nature of the putative progenitor star. Modeling the light curve is a powerful method to derive the physical properties independently of direct progenitor analyses. Aims. We investigate the physical nature of SN 2023ixf based on a hydrodynamical modeling of its bolometric light curve and expansion velocities during the complete photospheric phase. Methods. A grid of one dimensional (1D) explosions was calculated for evolved stars of different masses. We derived the properties of SN 2023ixf and its progenitor by comparing our models with the observations. Results. The observations at t & 20 days are aptly reproduced by the explosion of a star with zero-age main sequence mass of MZAMS = 12 M , an explosion energy of 1.2 × 1051 erg, and a nickel mass of 0.05 M . This indicates that SN 2023ixf was a normal event. Our modeling suggests a limit of MZAMS < 15 M , thereby favouring the low-mass range among the results from pre-explosion observations.